Burkholderia gut symbionts enhance the innate immunity of host Riptortus pedestris. Issue 1 (November 2015) - Kim, Jiyeun Kate; Lee, Jun Beom; Huh, Ye Rang; Jang, Ho Am; Kim, Chan-Hee; Yoo, Jin Wook; Lee, Bok Luel
Abstract The relation between gut symbiosis and immunity has been reported in various animal model studies. Here, we corroborate the effect of gut symbiont to host immunity using the bean bug model. The bean bug, Riptortus pedestris, is a useful gut symbiosis model due to the monospecific gut symbiont, genus Burkholderia. To examine the effect of gut symbiosis to host immunity, we generated the gut symbiont-harboring (symbiotic) insect line and the gut symbiont-lacking (aposymbiotic) insect line. Upon bacterial challenges, the symbiotic Riptortus exhibited better survival than aposymbiotic Riptortus. When cellular immunity was inhibited, the symbiotic Riptortus still survived better than aposymbioic Riptortus, suggesting stronger humoral immunity. The molecular basis of the strong humoral immunity was further confirmed by the increase of hemolymph antimicrobial activity and antimicrobial peptide expression in the symbiotic insects. Taken together, our data clearly demonstrate that Burkhoderia gut symbiont positively affect the Riptortus systemic immunity.